Harmonizing Dispute Resolution Mechanisms: Enhancing Efficiency and Synergy between WTO and ISDS System - Jillani, Muhammad Abid Hussain Shah; Bashir, Sobia; Khan, Faisal Shahzad (Pakistan Journal of Humanities and Social Sciences, 2023)
This research article explores aligning and optimizing dispute resolution mechanisms in international law, particularly within the World Trade Organization (WTO) and Investor-State Dispute Settlement (ISDS) contexts. Addressing challenges arising from the "spaghetti bowl effect" of multiple treaty regimes, it examines the interplay between WTO and ISDS systems, aiming for harmonization and reduced jurisdictional inconsistencies. Traditional coordination methods are evaluated, revealing limitations in adapting to this evolving paradigm. Instead, an "articulation clause" and the "principle of comity" are proposed as innovative approaches for rationalizing dispute resolution. These strategies aim to transcend rivalry between WTO and ISDS mechanisms, expediting impasse resolution in the WTO Appellate Body. The study promotes a strategic shift, encouraging stakeholders to view dual mechanisms as mutually advantageous. This pragmatic outlook empowers informed decision-making, enhancing the global rule of law's predictability, efficiency, and integrity. The ultimate goal is strengthening the WTO's dispute resolution framework and ISDS mechanism, contributing to a more streamlined and cohesive international dispute resolution landscape. The qualitative research methodology has been applied to the following article.